Fontes protéicas de origem vegetal em dietas para juvenis de carpa húngara (Cyprinus carpio) - Bergamin, Giovani Taffarel (2009)
This work aimed to evaluate the effect of replacing dietary porcine meat meal by different plant-protein sources on the growth, carcass yield, carcass quality, blood parameters and sensory evaluation of the fillets of common carp juveniles. Two experiments were conducted using water re-use system with 15 tanks (280L). In experiment 1, five experimental diets containing plant-protein sources were evaluated (soybean meal - FS, canola meal - FC, sunflower meal - FG and linseed meal - FL) to replace porcine meat meal (FCS - control diet). Common carp juveniles (195, initial weight 43.41g), were randomly distributed in the experimental units, and fed twice daily (09:00 and 15:00) with each of experimental diets, in triplicate. At the end of the trial (71 days), the best growth results were obtained in FCS, followed by FC and FS treatments that did not differ among each other. FCS, FG and FS had the highest values of corporal fat, while FC and FL diets did not show difference. The FL diet showed the worst growth, retention of protein and protein and fat deposition in whole body and fillet. About blood parameters, lower cholesterol was observed in the FG diet and lower aspartate aminotransferase activity was observed in the FL. The other variables did not differ significantly among themselves. Based on the results of experiment 1, the diets of experiment 2 were formulated, which were levels of replacement (0, 25, 50, 75 and 100%) of porcine meat meal by mixing canola meal + soybean meal. The juveniles (135, initial weight 238.05g), were fed 3% of biomass twice daily (09:00 and 15:00). At 18, 36, 54 and 72 days, linear negative effect of plant-protein inclusion for all parameters of growth was observed, except for condition factor. The same result was obtained for whole body fat deposition, fat and protein deposition in fillet and the total cholesterol in serum. Hemoglobin and hematocrit presented quadratic effect. The other measured parameters were not influenced by diets. Based on this results, we can conclude that a diet based on porcine meat meal provides better growth of common carp juveniles compared to plant-protein based diets, besides increased protein deposition in whole body and fillet; the carcass parameters (yield and digestive indexes) are not affected by the dietary protein sources; color and taste are not affected by the plant-protein based diets; there is linear negative effect of replacing porcine meat meal by the mixture of canola and soybean meal on the growth of common carp juveniles.